PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL BUGIS DI SDN LAUTANG KECAMATAN BELAWA KABUPATEN WAJO - Andi Eka Rezkianah; Rosleny Babo; Muhlis Madani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Character education has become widespread in the education world nowadays. Character education requires educators to contribute fully in the cultivation of character values to realize a civilized nation by maintaining local knowledge of each in every area that eroded due to shifting of the age. This study aims to describe the character education based on local wisdom (Bugis) in primary school SDN Lautang Belawa Wajo District of South Sulawesi. This research was a qualitative research using a case study with the observation method by looking at direct activities at school, interview to learn the characters that were applied at school, and documentation by looking at the results of report cards or portfolios of students. The result showed that the implementation of the character based on local wisdom that consists of obedience to God almighty (mapatoh ri Dewatae), honest (ma lempu), discipline (ma patoh), hard work (ma reso temangingi), responsible (Soppo: renge), love for the homeland (ma ri poji wanuata), peace-loving (siamaseang) were not completely applied and still needed to be evaluated. Supporting factors were the motivation of parents and school cooperation then inhibiting factors were the facilities, rules, learners’ background, lack of awareness of learners, and learners’ social environment. The conclusion of the research was the implementation of character based on local wisdom from several findings of the character value has not been seen and was well implemented.